A novel piezoelectric linear actuator designed by imitating skateboarding movement. (7th October 2020) - Wang, Kuifeng; Li, Xuan; Sun, Wuxiang; Yang, Zhixin; Liang, Tianwei; Huang, Hu
Abstract: By imitating skateboarding movement, a novel stick–slip piezoelectric linear actuator was proposed in this study. A specific flexure driving foot mechanism (FDFM) was designed to realize the bionic driving function, and theoretical analysis was conducted to calculate the displacement amplification ratio of the FDFM which was further confirmed by finite element simulation. Being different from most of previous design that the slider moved and the driving mechanism was fixed, here the FDFM was integrated with the slider and they moved together along the guide rail. Being similar to that the train moved along the tracks, this kind of layout would facilitate the realization of larger working stroke of the actuator. By experiments, output characteristics of the designed actuator under various driving frequencies and voltages were tested. The results showed that by changing the waveform of driving voltage, both forward and reverse motions with good linearity and stability could be easily achieved. The speed of reverse motion was higher than that of forward motion because of the relatively larger backward motion during forward motion, which was due to the promotion of deformation recovery of the FDFM. Furthermore, the resolution and loading capacity were characterized. The resolutions of forward and reverse motions were 47 nm and 45 nm, respectively, and the actuator could achieve a relatively stable speed when the vertical load was in the range of 0–2 N. This study is expected to provide a new idea for designing piezoelectric actuators with features of high speed, high stability and large working stroke.